Closure versus non closure of the subcutaneous fat layer of 2cm and more to prevent the incidence of wound disruption: an observational study - Dass, Anil G. Krishna (2005)
Introduction: Wound disruption is a known complication of caesarean section, which may cause additional and unnecessary morbidity to the patients. Its occurrence is influenced by many factors, of which technique of operation is one of the contributing factors. This study was carried out in order to determine whether closure of subcutaneous fat layer measuring 2cm or more will reduce the incidence of post caesarean wound disruption. Methods: Patients whose subcutaneous fat thickness of 2cm or more, underwent caesarean section were randomised into closure group and non- closure group. In the closure group, the subcutaneous fat layer was stitched while those in the ~on- closure group was not stitched. The result of wound healing was observed en the third, tenth and 42"d post- caesarean. Result: 120 patients were recruited into the study, with 60 samples were available for each group. There was 1. 7 percent of wound disruption occurred on the third day of caesarean section for each arm. Ten percent of wound disruption was noted to occur on the tenth day in the closure group as compared to 35 percent for the non .. closure group (p value 0.001 ). No wound disruption was noted on the 42"d day post caesarean section for closure group, while 3.3 percent was noted for the non- closure group, but not statistically significant. Conclusion: Closing the subcutaneous fat tissue measuring 2cm and above for patients undergoing caesarean section may help to reduce the occurrence of wound disruption post caesarean section.